Magnetic Analysis of Electromagnetic Microgenerator via Finite Element Analysis - W., Chin Chye; Z., Dahari (2011)
In future, micro sensor system will be deployed throughout our environment for monitoring pur-pose. Powering system is becoming important factor for independent and long period deployment sensors in our environment (deploy and forgot).